Spatial modulation of repetition blindness and repetition deafness. - Soto-Faraco, S; Spence, C (2001)
When two identical visual items are presented in rapid succession, people often fail to report the second instance when trying to recall both (e.g., Kanwisher, 1987). We investigated whether this temporal processing deficit is modulated by the spatial separation between the repeated stimuli within both audition and vision. In Experiment 1, lists of one to three digits were rapidly presented from loudspeaker cones arranged in a semicircle around the participant. Recall accuracy was lower when repeated digits were presented from different positions rather than from the same position, as compared to unrepeated control pairs, demonstrating that auditory repetition deafness (RD) is modulated by the spatial displacement between repeated items. A similar spatial modulation of visual repetition blindness (RB) was reported when pairs of masked letters were presented visually from either the same or different positions arranged on a semicircle around fixation (Experiment 2). These results cannot easily be accounted for by the token individuation hypothesis of RB (Kanwisher, 1987; Park and Kanwisher, 1994) and instead support a recognition failure account (Hochhaus and Johnston, 1996; Luo and Caramazza, 1995, 1996).